Biocontrol of Moler Diseases (Fusarium oxysporum f. sp capae (Snyder and Hans)) on Shallot with Endophytic Bacteria - Resti , Zurai; Darnetty, Darnetty; Khairul , Ujang; Reflin , Reflin; Siregar , Sri Lestari Kurnia; Tores, Farah Nabila (Journal of Applied Agricultural Science and Technology, 2024)
Fusarium Basal Root (FBR) disease locally known as "moler", caused by Fusarium oxysporum f.sp cepae (FOCe), poses a significant threat to Indonesian shallot cultivation, leading to yield losses of approximately 50%. Therefore, this research aims to identify endophytic bacteria with optimal capabilities to combat FOCe infection while improving shallot growth and yield. Randomized Completely Block Design (RCBD) consisting of seven treatments was used, including six different strains of endophytic bacteria (Bacillus cereus P14, Bacillus cereus Se07, Bacillus sp. HI, Bacillus sp. SJI, Serratia marcescens ULG1E2, and Serratia marcescens JB1E3) and a control, each treatment was replicated three times, and three plant units in each replication. The introduction of endophytic bacteria was performed through the bulb soaking method before planting, while FOCe suspension was inoculated to shallot growing media 4 weeks after planting. Parameters Variables such as moler disease development, plant growth, and shallot bulb weight were monitored. The results showed that endophytic bacteria effectively suppressed moler disease and boosted shallot growth and yield compared to the control. Specifically, S. marcescens JB1E3 showed 52.25% effectiveness in reducing moler disease severity, while S. marcescens ULG1E2 increased shallot yield by 65.50%.